PSIKOLOGI MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KEPUASAN KERJA GURU DI MA AL-WASHLIYAH KEDAISIANAM - Suwandi, Suwandi; Hia, Ayu Rahmini; Sakinah, Anggita; Ritonga, Gunawan; Ihsanadi, Ihsanadi (Al Ittihadu, 2022)
The principal's leadership has and plays a very important role in determining the level of teacher job satisfaction in the school he leads. Job satisfaction contains aspects of physical, psychological, and work environment. The leader's attention to subordinates can determine the level of job satisfaction. Management psychology in leadership is very important in increasing teacher job satisfaction. This study discusses how the principal's leadership in increasing teacher job satisfaction. The method used in this research is descriptive research method, data collection techniques used are observation and interviews. The results obtained in this study are teacher satisfaction at MA Al-Washliyah Kedaisianam towards the work created by the leadership with the principal and the teacher's motivation to work. One of the factors that greatly affects teacher job satisfaction at MA Al-Washliyah Kedaisianam is the leadership of the principal. Leadership support for job satisfaction is needed and needs to be created in schools, so that teachers can work with high morale, discipline, enthusiasm, dedication and live their profession